Study on Active Ingredient of Ailanthus Leaves - Gu, Tianhao; Liu, Wanying; Huo, Qing; Yu, Xiao (Asian Journal of Chemistry, 2014)
The separation and purification of active ingredient of Ailanthus altissma leaf and the analyze compositions were performed. The active ingredient of Ailanthus altissma leaf is separated by thin layer chromatography followed by GC-MS. The results showed that the active ingredients of the leaf could be isolated successfully by using the techniques of TLC with ethyl acetate:petroleum ether:methanol = 25:71:4 as the developing solvent. The GC-MS showed that the major ingredient of leaf is 9,12-diene-octadecane acid with abundant alkylate, such like decane, tetradecane, heptadecane, octodecane, heneicosane and some of esters like phthalic isobutyl alcohol ester, 8,11-diene-18 methyl ester and eighteen methyl esters, etc.